(untitled) (The Research of Medical Science Review, 2025)
The objective of this study was to compare the outcomes of the Limberg flap and Karydakis flap procedures for the management of pilonidal sinus disease which is a chronic inflammatory condition affecting the sacrococcygeal region leading to pain, infection, and recurrence. Limberg flap and Karydakis flap procedures are differentiated in terms of recurrence rates, wound healing, complications, and patient satisfaction. This comparative clinical study was conducted at the Federal Government Polyclinic Hospital (PGMI) during 2024-25, involving a total of 118 patients. In the Limberg flap procedure, a rhomboid-shaped excision of the pilonidal sinus and surrounding tissue was performed to ensure complete removal of the diseased tissue, with a transposition flap designed from the adjacent gluteal region and rotated into the defect. In the Karydakis flap procedure, an elliptical excision was performed to remove the pilonidal sinus along with the surrounding affected tissue. A laterally based advancement flap was then created and transposed to cover the defect, shifting the incision away from the midline to reduce tension and minimize the risk of recurrence. Both Limberg flap and Karydakis flap procedures were found to be effective surgical options for pilonidal sinus disease. Karydakis flap method demonstrated advantages in terms of lower recurrence rates, faster wound healing, fewer complications, and higher patient satisfaction. The recurrence rate of the Karydakis flap group was 4%, which was lower compared to the recurrence level of 7% for the Limberg flap group. The mean wound healing time was shorter in the Karydakis flap group (16 days) compared to 22 days in the Limberg flap group. Postoperative pain scores (VAS) were 2.0 and 2.3 for the Karydakis flap and Limberg flap group respectively. The incidence of complications, including surgical site infections, seroma formation, and hematoma, was lower in the Karydakis flap group. Additionally, patient satisfaction scores were higher (8.8/10) for the Karydakis flap group, compared to (8.2/10) for the Limberg flap group.